Traffic analysis of a simplified two-dimensional elevator system. (September 2015) - So, Albert; Al-Sharif, Lutfi; Hammoudeh, Ahmad
The idea of multicar operation within one hoistway is not new. Two-car systems are currently available on the market, whereby the two cars travel with restricted independence because one car must always remain above the other. With recent advances in linear machines, systems with more than two cars in one hoistway will soon become possible. In this paper, the authors go one step forward by assuming that multiple cars can move in a two-dimensional plane either attached to the facade of the building or across a vertical slice within the building. The analysis has been restricted at this stage to incoming traffic only. It is assumed that elevator cars can move upwards, downwards as well as sideways. In this way, passengers can exit at a stop very close to their destinations. The foreseeable technology is discussed, and two configurations (denoted as setups A and B) are proposed. The traffic analysis equations for such a system are also derived. A simulation is then carried out for the two setups based on one-car operation. The simulation shows that the proposed two-dimensional elevator system can reduce the total traveling time of a passenger as compared with the conventional one-dimensional setup. The system is described as special because the number of hoistways is restricted (up to a maximum of 2). Practical application : This paper provides a practical way of evaluating the round trip time for two different two-dimensional elevator applications. It also then compares three different sizes of buildings and shows that the use of two-dimensional elevator arrangements is only feasible for building with more than 30 floors high by 30 rooms wide.